France’s Tax Policy – Selected Problems - Ciuman, Krystyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
This article discusses the following aspects of tax policy in France:– the macroeconomic situation and the public finances,– the characteristics of tax revenues,– problems associated with France’s tax policy.